2019
DOI: 10.1111/jfpp.14097
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced survival of Lactobacillus sp. in β‐manno‐oligosaccharides‐enriched low‐fat ice cream under simulated gastrointestinal stress

Abstract: Survival of probiotic Lactobacillus plantarum NCIM 2372 and Lactobacillus fermentum NCIM 2165 was studied in low‐fat ice creams enriched with prebiotic β‐manno‐oligosaccharides (β‐MOS) under simulated gastro‐intestinal stress. β‐MOS‐enriched synbiotic ice creams had better overrun values (up to 23%), brightness (up to 78.06), whiteness index (up to 72.3), consistency index (up to 1.11 Pa.sn), flow behavior (up to 0.67), and viscosity (up to 0.22 Pa.s) than low fat control. Viability of probiotic cultures in β‐… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 44 publications
(73 reference statements)
0
5
0
Order By: Relevance
“…The fiber of pitaya residue provides an adequate balance between the fractions, thus causing an improvement in flow resistance. It has been already reported that the effect of prebiotic dietary fibers and oligosaccharides addition in ice creams as fat replacers is positive to the viscosity and textural properties (Panwar & Kapoor, ).…”
Section: Resultsmentioning
confidence: 99%
“…The fiber of pitaya residue provides an adequate balance between the fractions, thus causing an improvement in flow resistance. It has been already reported that the effect of prebiotic dietary fibers and oligosaccharides addition in ice creams as fat replacers is positive to the viscosity and textural properties (Panwar & Kapoor, ).…”
Section: Resultsmentioning
confidence: 99%
“…Fat is a critical element of ice cream, because it enhances the consistency, texture, and stability of ice cream. Thus, the reduction of fat in ice cream must be carried out carefully in order to maintain its key characteristics (Panwar et al, 2019). The ice cream fat content was observed between 11.15% and 9.40% ( Table 2).…”
Section: Effect Of Jamun Pomace Powder Incorporation On the Fat Conmentioning
confidence: 99%
“…Ice cream is world-famous high-vital emulsified milk sweets made from air cells milk fat, colloidal protein, fortifiers (Ghandehari, Barzegar, Gavlighi, Sahari, & Mohammadian, 2020;Pintor, Escalona, & Totosaus, 2017), stabilizers, emulsifiers, sweeteners, and colors (Cavender & Kerr, 2020;Panwar, Shubhashini, & Kapoor, 2019). It is one of the most commonly offered and enjoyed by youngsters and other age people around the world (Ayar, Siçramaz, Ozturk, & Ozturk, 2018;Azari, Khomeiri, Ghafouri, & Aghajani, 2017;Caniyilmaz, Uçarkuş, & Karaman, 2016).…”
mentioning
confidence: 99%
“…Consumer preference for functional food products is majorly governed by the perception of sensory attributes such as color (Balthazar et al., 2017; Panwar & Kapoor, 2019). The L *, a *, and b * values of the osmotically dehydrated pineapple pieces infused with L. plantarum and L. casei were measured and the results are presented in Table 3.…”
Section: Resultsmentioning
confidence: 99%
“…Research and development of probiotic foods has traditionally focused on fermented dairy products like yogurt, kefir (Wang et al., 2020), and recently on products such as ice cream (Panwar et al, 2019). However, lactose intolerance in around 75% of world's population, milk protein allergy, high cholesterol content, and lifestyle choices such as vegetarianism and veganism represent some of the limiting factors impeding the growth of dairy‐based probiotic foods (Heenan et al., 2004; Prado et al., 2008).…”
Section: Introductionmentioning
confidence: 99%